The vanishing independent: adapting to the changing dynamics of drug trafficking organisations in Mexico - Guy, Roger (Global crime, 2022)
Organised Crime in Mexico has undergone considerable change since 2006 when violent competition between drug trafficking organisations (DTOs) intensified. This article explores changes in drug trafficking activities from the perspective of independent dealers in Mexico City. Based on in-depth interviews (N = 64) we conclude that freelance dealers are increasingly pressured to become affiliated with DTOs despite being reluctant to do so. Our data suggest that cartels are more successful in attracting independent dealers with few economic alternatives, than those who are able to support themselves with a combination of licit and illicit activities. Therefore, to the degree that illicit drug sales are essential for economic sustenance, we expect that drug dealing for a criminal organisation will become norm as independent dealer become drawn into cartel work as licit opportunities diminish. For this reason we expect that independent dealers will continue their decline as the prevalence of DTOs increase from the steady demand for illicit substances.